Parties as playful experiences - Leland Masek; Jaakko Stenros (Eludamos, 2024)
Partying is a widespread, understudied, and playful phenomena. Game Studies has seen great value from defining important concepts related to games since its inception. Foundational play and game scholars urged for a need to analyze parties and celebrations as a form of playfulness, yet there is little empirical Game Studies work enabling a deeper understanding of partying. Partying bears striking resemblances to games: inefficient use of resources, arbitrary rules, cultural group formation, and ongoing moral panics. There are also practical overlaps: games occur at parties and digital party games are quite popular. This work contributes to a deeper understanding of parties by analyzing 33 semi-structured interviews where individuals from a wide variety of cultural backgrounds had highly playful experiences at parties. A new theoretical conception of partying as a form of playfulness is proposed as a “phenomenon that creates an experience of social connection in a group mediated through a shared engagement-prioritizing activity”. This work concludes with a call for party studies to become a sub-field in game studies.